2014
DOI: 10.1080/15732479.2014.887122
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of using basic, imprecise or uncertain data for elaborating sewer inspection programmes

Abstract: Published online: 26 Mar 2014International audienceOne key goal of sewer inspection programmes is to target segments in the worst condition. Despite the development of deterioration models, the influence of available data on models' predictive power has not been studied in depth yet. In this article, numerical experiments have been conducted to answer three main questions: (1) How can the data most probably available within a utility be used to define an effective inspection programme? (2) Can we use an auxili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Safety culture assessment requires the selection of an appropriate model, data gathering, and techniques to obtain measurable and repeatable assessment results (Maddin and Shanks, 2016). Substantial numbers of models have been presented since the introduction of the concept of safety culture (Ahmadi et al, 2014;Maddin and Shanks, 2016). Moreover, the negative relationship between HSEMS and workplace accidents and injuries show that the existing HSEMS are either ineffective or lack the acceptable safety standards to control hazard exposures in the industry.…”
Section: Figure 1: Borneo Mapmentioning
confidence: 99%
“…Safety culture assessment requires the selection of an appropriate model, data gathering, and techniques to obtain measurable and repeatable assessment results (Maddin and Shanks, 2016). Substantial numbers of models have been presented since the introduction of the concept of safety culture (Ahmadi et al, 2014;Maddin and Shanks, 2016). Moreover, the negative relationship between HSEMS and workplace accidents and injuries show that the existing HSEMS are either ineffective or lack the acceptable safety standards to control hazard exposures in the industry.…”
Section: Figure 1: Borneo Mapmentioning
confidence: 99%
“…The optimal dataset as defined by Tscheikner-Gratl et al (2013) does not exist. Ahmadi et al (2014a) showed that having a dataset with a high uncertainty is preferable to an incomplete dataset missing certain types of information (e.g. At least a representative sample, meaning that the overall condition of the sample must be close to the overall condition of the network, has to be obtained (Ahmadi et al, 2014b).…”
Section: Comparison With Rehabilitation Plans Of the Operatormentioning
confidence: 99%